2006
DOI: 10.1177/1052562905280845
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Transtheoretical Model of Change to the Sequencing of Ethics Instruction in Business Education

Abstract: Although there is widespread agreement on the importance of ethics instruction in business education, there is not agreement on the best approach or timing of instruction. This article uses J. O. Prochaska and DiClemente's transtheoretical model of change as the basis for a developmental model of studentreadiness for learning about ethics. By focusing on student development, the model suggests how to best sequence educational activities in ethics instruction. After introducing the model, it is applied to this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…Narayan, Steele-Johnson, Delgado, and Cole (2007) examined participants in an intervention program for driving under the influence (DUI) offenders, and found significant relationships between stage designation with perceived choice to attend training, perceived social support, and motivation to learn. Finally, Tyler and Tyler (2006) provide a perspective on the application of the TTM to the teaching of business ethics in the undergraduate classroom. It is in this direction that we feel that the TTM holds potential value for guiding interventions intended to improve the effectiveness of training in general, and e-learning in particular.…”
Section: A Theory Of Behavior Changementioning
confidence: 99%
“…Narayan, Steele-Johnson, Delgado, and Cole (2007) examined participants in an intervention program for driving under the influence (DUI) offenders, and found significant relationships between stage designation with perceived choice to attend training, perceived social support, and motivation to learn. Finally, Tyler and Tyler (2006) provide a perspective on the application of the TTM to the teaching of business ethics in the undergraduate classroom. It is in this direction that we feel that the TTM holds potential value for guiding interventions intended to improve the effectiveness of training in general, and e-learning in particular.…”
Section: A Theory Of Behavior Changementioning
confidence: 99%
“…Several researchers have observed that ethics instruction and perceptions of ethical culture are related to the moral development of students (Desplaces, Melchar, Beauvais, & Bosco, 2007;Kashyap, Mir, & Iyer, 2006;Tyler & Tyler, 2006). In particular, ethical instruction results in a greater reflection and ethical discussions on part of students before ethical actions are embarked upon.…”
Section: Goals Of Business Ethics Educationmentioning
confidence: 98%
“…A well-informed and well-designed intervention is needed to complement and support effective organisational change. Furthermore, organisations are more effective in bringing about change when the intervention matches their stage of change Tyler & Tyler, 2006). Stage-matched interventions THIS STUDY ASSESSES FAMILY day care educators' readiness for increasing their knowledge and skills in promoting children's social and emotional wellbeing by applying the Transtheoretical Model of Change conceptual framework.…”
Section: Building Capacity For Change Within Organisationsmentioning
confidence: 99%
“…Relevant to the current paper is that the TTM has also been applied to address organisational changes (Berry et al, 2007;Clark, 2013;Glanz & Bishop, 2010;Tyler & Tyler, 2006). Clark (2013) described how the comprehensive framework of the TTM can provide key multidimensional information that is essential to facilitate and maintain organisational change.…”
Section: The Transtheoretical Model Of Changementioning
confidence: 99%